Analysis on the cause of packet loss in wireless networks. - Teh, Terry (2022)
WSN (Wireless Sensor Network) is a new technology that has a lot of potential for both civilian and military uses in the future. With the wide adoption of WSN, ensuring data accuracy is a must for decision making in the sensing area of the system. However, the combination of sensor technologies, computational power, and wireless connectivity makes it lucrative to be exploited in large quantities. Every packet contains the information sensed by the sensor node in the sensing system and deliver to the Base Station (BS) as a statistic for the end-users to further analyse. In WSN, intermediate-quality links frequently generate vulnerable connectivity, but packet losses induced by such volatile links are difficult to track. A packet loss implies that the information sent to the end-users will result in an inaccurate state. Thus, it might affect the end-users decision making on the sensing system. In previous studies, packet loss rate in WSN is a very common issue that every expert tried to minimize. Notwithstanding, very few studies or none of them are discussing identifying the actual reason for the packet loss. Without identifying the actual reason for the packet loss, the effectiveness of packet loss responses can be harmed, one might continue suffering from the problem of packet loss because of being unable to troubleshoot it. This project intended to propose a lightweight analysing scheme to identify the reason packet loss is due to network issues or malicious discard. The analysing scheme may also be used to enhance the current Intrusion Detection System (IDS) as nowadays most of them are only capable of detecting packet loss. Lastly, having an analysing scheme to identify the reason for packet loss can improve the effectiveness of packet loss responses, thus one will not be continuing to receive inaccurate data from the sensing nodes. This project will verify the proposed analysing scheme by using a network simulation through the OMNeT++ network simulator and INET framework. A selective forwarding attack will be used to emulate the malicious discarding of the packet and a radio interferer will generate radio interference to emulate the network issues in the network model.